Nanostructured systems containing essential oil of lavender: current overview and future perspectives - Nedel, Sheila; Gundel, Samanta; Boeck, Carina; Ourique, Aline (Disciplinarum Scientia | Naturais e Tecnológicas, 2021)
The wide variety of aromatic plants and their use represent great economic value worldwide, due to the numerous therapeutic properties available. The Lavandula genus stands out in the world economy, mainly due to the production of essential oil, which can be extracted from its leaves or flowers, being widely used in the cosmetic, food and pharmaceutical industries. However, the therapeutic properties of this essential oil can be impaired due to its low aqueous solubility, high volatility and low physical-chemical stability. The association of essential oil with nanostructured systems can be a promising and efficient alternative to overcome these limitations, providing greater stability of the active compounds, protection against oxidation, photodegradation and thermal degradation processes, and thus, promoting a potential enhancement of efficiency. Thus, the objective of the study was to carry out a review of the literature about the available research that uses nanostructured systems to encapsulate the essential oil of different lavender species. The search was carried out in April 2020, in the electronic databases Web of Science, PubMed and ScienceDirect. The descriptors and keywords used were: nano *, lavender, Lavandula, followed by the Boolean operators AND; OR, and the year of publication of the articles was not defined. Eight articles were found that adequately met the inclusion criteria, which were published between the years 2017 to 2020. From the results found, it is believed that nanotechnology can be a promising alternative to protect the active compounds of lavender essential oil against factors that can impair their stability, as well as, guarantee or even increase their effectiveness, with the possibility of decreasing dose and consequently side effects.